Fit testing of KN95 masks - Caoili, Janice Campos; Vega, Arvee; Santos, Sigrid; Bigalbal, Jomar; Cabujat, Rosemarie (International Journal of Infection Control, 2020)
Twenty-six healthcare workers (HCWs) underwent qualitative fit testing for donated KN95 masks. For each fit test episode, the result was either passed or failed. Results for a total of 42 fit test episodes were observed. A result of failed was recorded for 39 of 42 fit test episodes. Various adjustments such as tightening the ear loops to produce a better fit, placing a surgical mask either under or over the KN95 mask, and wearing the K95 mask with a coverall, were done but the result of testing was failed. As fit testing all HCWs in the hospital would be excessively time-consuming, the findings of this fit-testing study served as the basis for a hospital memorandum stating that KN95 masks are not generally recommended for use by HCWs while performing aerosol-generating procedures in the COVID-19 units. HCWs who might use KN95 masks while performing aerosol-generating procedures should first undergo fit-testing to ensure that a good seal is achieved for protection against infectious aerosols.